Study on the Potential of Bebubus Batu in Introducing the Local Culture of the Sasak Tribe in Early Children - Sunandar Azmaul Hadi; Sopian Ansori; Mariawati Mariawati (International Journal of Educational Narratives, 2024)
Background. Several local cultures of the Sasak tribe are threatened with extinction, one of which is Bebubus Batu. Preserving this culture needs to be done from an early age. Therefore, it is necessary to prepare learning tools based on local wisdom in early childhood education units. Bebubus Batu can be incorporated into learning in the form of a fairy tale Purpose. This research aims to develop learning tools in the form of fairy tales based on the local wisdom of the Sasak tribe, namely the Bebubus Batu culture. Method. This research involved the community, religious leaders, traditional leaders, and early childhood education teachers. The data was then analyzed using a descriptive qualitative approach Results. Research findings show that bebubus batu culture can be presented to young children in the form of fairy tales because it contains noble values such as (1) Respect for food as a product of the earth. (2) cooperation. (3) Belief in supernatural things. (4) Be wise in managing natural resources. (5) Strengthen ties of friendship. Conclusion. Bebubus Batu culture can be used as a medium for learning fairy tales in early childhood education units because it contains noble values